Social stress and psychiatric disorders: Evolutionary reflections on debated questions. (September 2020) - Troisi, Alfonso
Highlights: Evolutionary theory clarifies the link between social stress and mental disorders. Social stressors interfere with the achievement of biological goals. The severity of the stressor correlates with the importance of the biological goal. There is a natural hierarchy of biological goals. Life history strategies impact stress sensitivity and stress generation. Abstract: The literature on social stress and psychiatric disorders is biased toward proximate explanations. While it is important to know how the mechanisms implicated in social stress operate, we also need to learn why selection has retained those mechanisms. This review analyzes debated questions from the perspective of Darwinian psychiatry: What is a stressful event? Why are certain types of stressful events particularly potent? Why don't stressful events fall randomly from the sky? Why does life stage modulate the impact of stressful events? Why are some people more resilient or vulnerable to stressful events? Why are there sex differences in stress sensitivity? Are specific stressful events linked to specific disorders? An evolutionary perspective can increase and broaden our understanding of why exposure to different types of social stress triggers the onset of psychiatric disorders. The application of evolutionary concepts not only clarifies and contextualizes how certain social experiences are implicated in the etiology of psychiatric disorders; it can also steer researchers toward novel hypotheses not anticipated by traditional models.